2003
DOI: 10.1515/jpm.2003.047
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal outcome of growth discordant twin gestations

Abstract: The aim of the study was to compare a variety of neonatal outcome variables of growth concordant twin gestations (CT) to that of growth discordant twins (DT). Maternal and neonatal charts of live, non-anomalous twins > 25 weeks' gestation from 1984-2000 with no evidence of twin-twin transfusion syndrome were reviewed for several variables. DT occurred in (N = 81) 11.9% of all twin pregnancies. In 61.7% of DT, twin B was the smaller of the twins. There was no difference in maternal age, admission indications, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 21 publications
1
19
2
Order By: Relevance
“…In another study, it was found that discordant twins had a significantly higher incidence of SGA status than concordants but there was no difference for neonatal complications. 24 In our study, while the incidence of hypoglycemia was significantly higher in discordant twins, sepsis was significantly more frequent in concordant twins. The increased incidence of sepsis in our series could not be attributed to LBW or lower gestational ages of the babies, since these parameters were similar in both groups.…”
Section: Discussionsupporting
confidence: 42%
“…In another study, it was found that discordant twins had a significantly higher incidence of SGA status than concordants but there was no difference for neonatal complications. 24 In our study, while the incidence of hypoglycemia was significantly higher in discordant twins, sepsis was significantly more frequent in concordant twins. The increased incidence of sepsis in our series could not be attributed to LBW or lower gestational ages of the babies, since these parameters were similar in both groups.…”
Section: Discussionsupporting
confidence: 42%
“…(6,7) Hollier et al have shown that higher BWD was a risk factor for HMD, (26) although Nassar et al did not find any such association. (25) HMD was observed in about 12% of twin infants in our study, and only prematurity and lower birth weight were identified as independent risk factors.…”
Section: Discussionmentioning
confidence: 49%
“…(6) Nassar et al reported a 1% incidence of neonatal seizures in twins, (25) and Hollier et al found higher BWD to be a risk factor for neonatal seizures. (26) In our study, seizures were seen in about 4% of twin infants, and the most common aetiology was hypoglycaemia, followed by HIE and hypocalcaemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations